Statutory civil remedies in trade mark litigation - Kelbrick, Roshana (University of South Africa, 1997)
Little attention is paid to the civil remedies available when infringement of a trade mark or the right to goodwill occurs. Yet, for the owners of ~uch rights, these remedies are of much greater importance than theoretical considerations regarding the nature of the rights or what constitutes their infringement. This thesis analyses the civil remedies for trade mark infringement granted by the South African Trade Marks Act 194 of 1993. In the South African context, any consideration of civil remedies is rendered problematic by the attempted graft of English remedies onto a legal system with a different common-law background. It is, therefore, essential first to trace the English origin and application of these remedies, and then to determine whether each remedy is acceptable in terms of the South African common law. This is necessary, as our courts have previously rejected or adapted English remedies which were unknown to our common law but which Parliament introduced in legislation. The remedies of interdict (or injunction) in final and interlocutory form, compensatory damages, reasonable royalties, and delivery up are analysed from a substantive law and a procedural perspective. The procedural innovation of an inquiry as to damages is also considered. In respect of each remedy, (1) the English roots and development of the remedy are traced; (2) differences of approach in two other Commonwealth jurisdictions, Australia and Canada, are highlighted; (3) the development of the South African equivalent is detailed; and (4) suggestions for the future implementation of the remedy in South Africa are made. In the penultimate chapter, our common law and legislation (including the Constitution of the Republic of South Africa 108 of 1996 ) are measured against the requirements of the Agreement on Trade-related Aspects of Intellectual Property Rights (TRIPS). Recommendations for the effective utilization of each remedy in South Africa are then made. They include suggestions for legislative amendment in respect of delivery up and an inquiry as to damages, and the introduction of statutory damages as an further civil remedy.
Keywords: Civil remedy; Intellectual property; Trade marks; Trademark dispute; Trademark litigation

Restraint of trade at common law - Dempster, Hamish Leslie (University of Auckland, 1997)
This is a collection of essays about the restraint of trade doctrine as laid down in the courts of the United Kingdom and the British Commonwealth. Generally, I will not give an account of the restraint of trade doctrine in the United States of America, for even although each individual state (apart from the civil jurisdictions California and Louisiana) and the federation itself, has a common law system, for reasons peculiar to those jurisdictions, the restraint of trade case law there has become so vast and so confused as to be unsuitable for my purposes. More importantly, however, the common law restraint of trade doctrine in the United Kingdom and the British Commonwealth has been laid down by courts without any significant consideration of the state of the law in the United States. Davies v Davies (1887) 36 Ch D 359, 370 by contrast, the period during which the Privy Council operated as a supra national court of final appeal has resulted in considerable harmony in the doctrine within the British Commonwealth. Even now the House of Lords is influential in Australia and Canada and the influence is increasingly reciprocal. By way of an exception I will discuss the purposes of the anti-trust legislation in the United States. This is necessary because I intend to show that the common law restraint of trade doctrine was not able to be, and was never intended to be, a means of regulating the economy in contradistinction to the United States anti-trust legislation and related legislation in the British Commonwealth. This account is not merely a description of the law relating to the restraint of trade doctrine although I do purport to describe the law. There are other accounts of the restraint of trade doctrine which do that well. Accounts of the restraint of trade doctrine include: Matthews & Adler, The Law Relating to Covenants in Restraints of Trade (London, 2nd ed 1907); Sanderson, Restraint of Trade in English law (London, 1926); Heydon, The Restraint of Trade Doctrine (London, 1971); Trebilcock, The Common Law of Restraint of Trade; A Legal and Economic Analysis (Toronto, 1986); Dean, The Law of Trade Secrets (Sydney, 1990); Mehigan & Griffiths, Restraint of Trade and Business Secrets: Law & Practice (London, 2nd ed 1991); Holdsworth, History of English Law IV (3rd ed, 1945) 343-54, 373-9; VIII (2nd ed, 1937) 56-42. There are other, less detailed accounts in contract law textbooks. The purpose of this dissertation is to describe aspects of the doctrine as it developed between the medieval period and the twentieth century and then to use that account as a basis for an analysis of how the law has taken a number of paths during the twentieth century which cannot be justified by the rules and their justifications which existed in the law prior to that time. Such a development has had important consequences for the restraint of trade doctrine and even the law in general, most of which have been detrimental. I do not intend to give a continuous historical narrative covering the whole of the doctrine. The history has been described before. For example, I do not intend to give a discrete account of the process by which the absolute rule against general restraints of trade gave way to the rule of reason, although I do mention this process where relevant for other purposes. The history, so far as it is relevant, is integrated into each chapter. I will argue that historically the restraint of trade doctrine was a rule or complex of rules, of a certain form and content. The form and content of the rule are important because they bear on the meaning of the class term "restraint of trade" which is an element of the rule. The meaning of that term began to change around the year 1890. Beginning first with certain classes of trade combination, courts began to classify as restraints of trade covenants which did not in fact restrain trade. Then the courts similarly treated the exclusive dealing contract and certain forms of property transaction. Another trend in the law which added to the confusion about the meaning of restraint of trade was the failure by the courts to make definitive findings one way or another as to whether a particular covenant was in restraint of trade. The courts were then faced with a dilemma. The law required a court to refuse to enforce a covenant in restraint of trade unless the covenantee could justify the restraint by presenting evidence to the court from which the courts could assess whether or not that particular restraint was within the reason for the restraint of trade doctrine or not. Such considerations were entirely inapt in the case of covenants which, in accordance with the traditional view, did not restrain trade. Yet if the courts did not validate these contracts, catastrophic consequences would have followed for the parties to such contracts and, indeed, to contract as an institution. To solve the dilemma the courts began to interpret the famous statement of the restraint of trade doctrine by Lord Macnaghten in Nordenfelt v Maxim Nordenfelt Guns & Ammunition Co [1894] AC 535, 565 (HL) literally, rather than contextually. Ultimately this has resulted in the obscuring of the rule underlying the restraint of trade doctrine itself. There were many minor confusions along the way. It is important that the doctrine is coherent and its use consistent with its justifications because it is still a fruitful cause of legal change. In the last year the force of the rule has caused a radical restructuring of Association Football in Europe Bosman’s case. The rule has even penetrated the collective consciousness of the community at large. The broad thrust of the development and the detail will be outlined in the next thirteen chapters.

The principle of subsidiarity and its critique : a contextual analysis of the principle of subsidiarity - Estella De Noriega, Antonio (European University Institute, 1997)
Theorising again about a topic that has already received a great deal of scientific attention may be viewed, to use some well known words of Camus, as "the ultimately absurd act" (Camus, 1975). Precisely in order to avoid, when dealing with a classic topic, falling into the absurd, or what is only slightly better, into the banal, it is necessary to use afresh methodological and conceptual tools. This should allow one to pose new questions and, finally, open up new intellectual perspectives. Conversely, the distance that one is to cover needs to be not too far removed from current paradigms. Otherwise one may fall into a different kind of trap -that of offering a contribution which is interesting but totally useless, as it were, for the purpose of shedding new light on the ongoing debate. In fact the main trigger for embarking on this project was a reaction to what were current legal critiques of the principle of subsidiarity at a given moment. Though I conceded that a critical outlook should be taken as regards subsidiarity, and no mere review of the principle in legal-technical terms, the standard critique left me with the bitter taste of scientific dissatisfaction. In my view it seemed, at best, to entirely miss the point as regards the issues, that were raised by the introduction of subsidiarity into the constitutional order of the Community, which, in turn, implied that the answers that were given were also clearly unsuitable. I therefore underwent the effort of giving an alternative critical reading of the principle of subsidiarity, the result of which constitutes the thrust of this thesis. Yet before entering into the following critique, it is important to make, by way of introduction, a number of remarks concerning (i) the genealogy of this thesis; (ii) the method; (iii) conceptual issues; (iv) the exposition of the main research hypothesis according to which this work shall be conducted; and (v) the structure of this thesis.
Keywords: Principe de subsidiarité; Principle of subsidiarity

Airline labour law : a study of certain labour law rules in international air transport - Huang, Chu Cheng (McGill University, 1997)
This thesis examines problems related to particular labor laws currently applied in international air transport. This analysis is framed within the context of scholarly theory and judicial practice arising from various regimes of labor law governing industrial injury, the individual contract of employment, labor-management relations, and fair treatment in the civil aviation industry. A critical survey of labor regulations operating in the international air transport industry is provided through commentary on the principles formulated by judicial decisions and the theories which underlie their reasoning, helping to clarify both substantive and procedural labor laws affecting international air transport. A critical analysis of different categories of statutory labor law governing international air transport is also provided to assess the validity of commonly-erected conflict of labor law rules, thereby revealing the inadequacy of the single rule principle in view of the unique and perplexing regulatory interests which are inherent in aviation activity. The divergence between domestic labor statutes and Treaties of Friendship, Commerce and Navigation or bilateral air transport agreements also adds a more subtle aspect to the problems explored.
Keywords: Air transport; Airline; Droit du travail; Labour law; Labour relations; Transportation

States and markets : regulatory competition and the public law of banks - Padrós Reig, Carlos (European University Institute, 1997)
One of the most immediate questions that could be raised is that of the topic. Why banks?. Banks are a part of the economy which is especially prone to regulatory competition. Increasing financial globalization makes it difficult to maintain regulatory barriers and those remaining create costs that are avoided by regulatory arbitrage. Banks’ raw material is capital which is a highly mobile element. On the top of that, the longstanding experience of the US in the field, should be of some usefulness. Finally, banks are attractive since the European Union, by means of the Second Banking Directive, has undertaken a decisive step towards liberalisation. Regulatory competition in this field will be able to give us some clues into the direction of services regulation in general, and into the new institutional dimension of the Union. However, banks are only one type of financial actors. Securities and insurance industry are gradually occupying spaces traditionally reserved to banks - namely deposit collection and lending - and conversely, banks are extending their product range to cover securities and insurance activities, and are experiencing a process of disintermediation. Hence, it is increasingly impossible to distinguish among financial actors. Concentrating in one of them is just a research need in order to keep the study under manageable dimension. Still, banks remain a legally different industry because of their position in the economic gear and in the payment system. What could actually be questioned is the future of banks themselves or at least their different legal treatment In any case, the topic of financial services regulation is too large to be covered as a whole, so some subdivision is necessary. This has to be done acknowledging that divisions may not correspond to the reality of the marketplace.
Keywords: Banks; Competencia; Competition law; Law of Banks; Regulation